1977
DOI: 10.1111/j.1939-0025.1977.tb01269.x
|View full text |Cite
|
Sign up to set email alerts
|

Teenage status of hyperactive and nonhyperactive learning disabled boys.

Abstract: Three groups of learning disabled boys—hyperactives, normoactives, and hypoactives—were studied in grade school, reevaluated at fourteen. At follow‐up, all three groups remained at disadvantage to controls on academic and cognitive measures and on complex reaction time. Half the hyperactives had experienced major conflicts with authority, and over a third of hypoactives exhibited psychologically disturbing behaviors. Mental health of normoactives appeared comparable to controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0
1

Year Published

1980
1980
2011
2011

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(17 citation statements)
references
References 23 publications
1
15
0
1
Order By: Relevance
“…Lambert and Sandoval (1980) found that 42.6% of all hyperactive children would qualify as learning disabled using fairly stringent objective measures of ability/achievement discrepancies. Additional support for this speculation comes from a followup study (Ackerman, Dykman, & Peters, 1977) in which nonhyperactive learning disabled students exhibited levels of prosocial behavior and emotional stability comparable to average achievers at age 14, whereas half the hyperactive/learning disabled students had experienced major conflicts with authority by that time. These included trouble with school authorities, serious family conflict and acting out, plus placement in a state training school.…”
mentioning
confidence: 82%
“…Lambert and Sandoval (1980) found that 42.6% of all hyperactive children would qualify as learning disabled using fairly stringent objective measures of ability/achievement discrepancies. Additional support for this speculation comes from a followup study (Ackerman, Dykman, & Peters, 1977) in which nonhyperactive learning disabled students exhibited levels of prosocial behavior and emotional stability comparable to average achievers at age 14, whereas half the hyperactive/learning disabled students had experienced major conflicts with authority by that time. These included trouble with school authorities, serious family conflict and acting out, plus placement in a state training school.…”
mentioning
confidence: 82%
“…An early study comparing youngsters who were ADHD and learning disabled to youngsters who were learning disabled and did not have ADHD (Ackerman, Dykman, & Peters, 1977b) found that while about half of the ADHD group with LD engaged in antisocial behavior, only a small percentage of youngsters who were learning disabled and not ADHD had done so. In fact, the non-ADHD group with LD demonstrated levels of prosocial behavior and emotional stability that were comparable to those of average achievers.…”
Section: Susceptibility Hypothesismentioning
confidence: 99%
“…We have been struck over the years with the passivity of the non-hyperactive, learningdisabled school children who have participated in our research projects (e.g., Ackerman, Dykman, & Peters, 1977;Ackerman, Elardo, & Dykman, 1979). Passivity as a trait can be as much a hindrance to learning as overactivity.…”
Section: Interrelations Of Cognitive Achievement and Personality Varimentioning
confidence: 99%